2020
DOI: 10.1183/23120541.00250-2019
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional folic acid supplementation and risk of parent-reported asthma in children at 4–6 years of age

Abstract: BackgroundFolic acid supplementation is universally recommended for women of child-bearing age to prevent fetal neural tube defects (NTDs). Concerns have arisen over the potential risk for childhood allergy and asthma due to folic acid supplementation. We examined whether periconceptional supplementation with low-dose folic acid only was associated with an increased risk for allergy symptoms or asthma in offspring at 4–6 years of age.MethodsOut of 247 831 participating women enrolled in 1993–1996, 9090 were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Two later studies [ 137 , 138 ] indicated that folic acid supplementation, depending on when it was started (3 rd trimester vs. 1 st trimester or earlier) and how long it was taken, increased the risk of the development of childhood asthma. However, the data have to be interpreted with caution and were not confirmed by two current intervention studies [ 139 , 140 ]. It has also been indicated that the impact of folic acid supplementation on the child’s lung function could be modified depending on the presence of a gene polymorphism of methylenetetrahydrofolate reductase (MTHFR C677T polymorphism) in the pregnant woman [ 133 ].…”
Section: Discussionmentioning
confidence: 71%
“…Two later studies [ 137 , 138 ] indicated that folic acid supplementation, depending on when it was started (3 rd trimester vs. 1 st trimester or earlier) and how long it was taken, increased the risk of the development of childhood asthma. However, the data have to be interpreted with caution and were not confirmed by two current intervention studies [ 139 , 140 ]. It has also been indicated that the impact of folic acid supplementation on the child’s lung function could be modified depending on the presence of a gene polymorphism of methylenetetrahydrofolate reductase (MTHFR C677T polymorphism) in the pregnant woman [ 133 ].…”
Section: Discussionmentioning
confidence: 71%
“…These studies were published between 2006 and 2022, involving 252,770 participants, including 50,248 children with asthma. Seven studies were conducted in Europe ( 37 , 39 , 42 , 43 , 45 , 46 , 48 ), five in North America ( 35 , 36 , 38 , 40 , 49 ), four in Asia ( 32 34 , 44 ) and two in Australia ( 41 , 47 ). The included studies adjusted for potential confounders, such as maternal age, race, parity, education level, smoking history, asthma history, infant sex, birth weight, mode of delivery, and feeding method.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the scores for study quality ranged from 5 to 8. Twelve original studies ( 32 , 33 , 36 38 , 40 42 , 44 46 , 49 ) were assessed as high quality, and six ( 34 , 35 , 39 , 43 , 47 , 48 ) assessed as medium quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes have been associated with enhanced severity of allergic airway disease. (12) Several observational cohort studies have reported inconsistent associations between higher prenatal folic acid or folate intakes and risk of allergic disease in the offspring (13)(14)(15)(16) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) however many rely on dietary assessment to measure exposure. Of the studies that examined biomarkers to determine exposure, only one differentiated between specific forms of folate (20).…”
Section: Introductionmentioning
confidence: 99%